Synthesis of molecularly imprinted polymers of vanillic acid and extraction of vanillic acid from spiked blood serum - Showkat Ahmad Bhawani, Salma Bakhtiar, Rachel Roland, Syed Rizwan Shafqat, Mohamad Nasir Mohamad Ibrahim (Journal of Applied Pharmaceutical Science, 2020)
Vanillic acid (4-hydroxy-3-methoxybenzoic acid) is a phenolic acid found in many plant extracts. It is used as a flavoring and scent agent and produces a pleasant, creamy odor. It is widely used in many applications for therapeutic purposes to flavoring agent. Molecularly imprinted polymers of vanillic acid were synthesized by precipitation polymerization with a noncovalent approach for the extraction from blood serum. Three different imprinted polymers have been synthesized with varying molar ratio of monomer. The synthesized polymer particles were characterized using Fourier-transform infrared spectroscopy and scanning electron microscopy. The extraction efficiency of highly selected imprinted polymer of vanillic acid from spiked blood serum was about 80%.
Keywords: Vanillic acid, molecular imprinted polymer, precipitation polymerization, acrylic acid, ethylene glycol dimethacrylate.